Target highlights in CASP13: Experimental target structures through the eyes of their authors. Issue 12 (9th September 2019) - Lepore, Rosalba; Kryshtafovych, Andriy; Alahuhta, Markus; Veraszto, Harshul A.; Bomble, Yannick J.; Bufton, Joshua C.; Bullock, Alex N.; Caba, Cody; Cao, Hongnan; Davies, Owen R.; Desfosses, Ambroise; Dunne, Matthew; et al.
Abstract: The functional and biological significance of selected CASP13 targets are described by the authors of the structures. The structural biologists discuss the most interesting structural features of the target proteins and assess whether these features were correctly reproduced in the predictions submitted to the CASP13 experiment.